Antidermatophytic lead compounds from Streptomycetes albidoflavus STV1572a against Tinea infections by Tricophyton mentagrophytes. (May 2020) - Thekkangil, Aswani; Suchithra, T.V.
Abstract: Dermatophytic infection is a psychological burden due to its inefficacy in prolonged effectiveness during its course of treatment. The present study reports a novel antidermatophytic property from actinomycetes of wetlands soil. Total of 37 Streptomyces isolates were screened for antidermatophytic activity against Trichophyton mentagrophytes . The best isolate with 100% novel activity, was characterized and designated as Streptomyces albidoflavus STV1572a . Antidermatophytic compounds extracted from the mentioned strain were partially purified by chromatographic techniques. Further, it was characterized using UV–Vis spectroscopy, FTIR spectroscopy, and GC-MS analysis. Compound identified were, Phenol 2, 4-bis (1, 1-dimethylethyl), 9-octadecene (E), E−14- Hexadecenal, e−15- Heptadecenal, 1- Heneicosanol, Hypophosphonousdichloride bis (1, 1-dimethylethyl) and Heptadecyl trifluoroacetate. To sum up, this study illustrates an antidermatophytic lead compounds that pave its way for further purification and characterization of these compounds for their optimum utilization for antimycotic purposes. Graphical abstract: Image 1 Highlights: Trichophyton mentagrophytes a contagious fungus is causative agent of Tinea infection. Prolonged medication needed to treat Tinea infections. Streptomycetes albidoflavus STV1572a, wetland actinomycetes explore for antidermatophytic activity. Partially purified GC-MS result revealed eight compounds imparted the antidermatophytic activity.